Evaluation of the Obesity Prevention, Blood Glucose, and Blood Lipid Control of Vietnamese Rice Varieties in High-Fat Diet-Induced Obese Mice - Thuy Linh Nguyen; Khanh Son Trinh (International Journal of Food Science)
Five Vietnamese rice varieties, which differ in their basic chemical composition (starch content, amylose content, fiber content) including polished rices and whole grain rices, were chosen for this study. High-fat diet-induced obesity, using these rice, was subjected to in vivo experiments to evaluate the effects of body weight gain, caloric intake, postprandial blood glucose level (PBGL), and glycemic index (GI) in tested mice groups. PBGL peaks appeared at 30th minute after eating, and GI of each experimental group was ranked in order as GN>TL>HR>GM>LĐ and GN>LT>HR>LĐ > GM, respectively, in which, brown rice (LĐ) and germinated brown rice (GM) had low GI. Furthermore, these rice varieties caused the lowest LDL cholesterol and the ratio of LDL/HDL cholesterols in mice. In this study, the higher the amylose and fiber contents were, the lower glycemic index, triglycerides, LDL, and LDL/HDL values were. The golden flower glutinous rice (GN), with low amylose and fiber content, gave worse blood lipid parameters than that of GM and LĐ. Histopathological studies of white adipose and liver tissues showed that LĐ and GM significantly reduced the symptoms of obesity and fatty liver compared with the others, especially compared to GN. The results obtained from this study help patients with overweight, obesity, and type 2 diabetes choose the right rice variety for their daily diet to be able to control their diseases.